Radiotherapy dose limit for uterus fertility sparing in curative chemoradiotherapy for rectal cancer - Lohynska, Radka; Jirkovska, Michaela; Novakova-Jiresova, Alena; Mazana, Eva; Vambersky, Kamil; Veselsky, Tomas; Kindlova, Anna; Stankusova, Hana; Malinova, Bela (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2021)
AIMS: Curative sphincter sparing radiotherapy is a treatment option for early rectal cancer. There are many methods developed for fertility preservation in young patients treated with pelvic radiotherapy. Pregnancy rates after radiotherapy are dependent on the radiation dose to ovaries and uterus. Data on outcomes of total body irradiation suggest a pregnancy is possible following 12-14 Gy TBI, despite elevated rates of preterm deliveries and other complications. METHODS: We report a case of full-term delivery of twins after curative chemoradiotherapy for anorectal adenocarcinoma T2 N0 M0 with the total dose 58.6 Gy. The patient underwent laparoscopic laterocranial ovarian transposition before radiotherapy. RESULTS: Long term complete remission was achieved after treatment. Although a spontaneous conception was not successful, the patient underwent an in vitro fertilisation procedure with donor eggs and conceived twins 10 years after the radiotherapy treatment. The mean dose to the uterus was 16 Gy and to the uterine cervix 35 Gy. She reached a full-term pregnancy and delivered two healthy babies by caesarean section at a gestational age of 38 weeks, weighing 2420 g and 2220 g. CONCLUSION: This is the first case report of the successful pregnancy following sphincter sparing curative pelvic radiotherapy for rectal cancer. Furthermore it allows us to propose an increased limit dose to the uterus enabling fertility sparing beyond the limits achieved from total body irradiation series with 12-14 Gy and accept 16 Gy as uterine body (35 Gy for uterine cervix) limit for IMRT treatment planning in young patients asking for maintaining fertility potential.
Keywords: těhotenství; Uterus; Radiotherapy Dosage; celková dávka radioterapie; výsledek těhotenství; uterus; chemoradioterapie; adenokarcinom; léčba šetřící orgány; Adult; zachování plodnosti; Fertilization in Vitro; fertility sparing; rectal adenocarcinoma; uterus dose; ženské pohlaví; nádory rekta; Humans; Pregnancy; radiotherapy; dose constraints; Pregnancy Outcome; fertilizace in vitro; Rectal Neoplasms; Organ Sparing Treatments; dospělí; Female; Adenocarcinoma; Chemoradiotherapy; lidé; Fertility Preservation